The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1002/j.1460-2075.1988.tb03024.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma delta transposase and integration host factor bind cooperatively at both ends of gamma delta.

Abstract: gamma delta, a prokaryotic transposon, encodes a transposase that is essential for its transposition. We show here, by DNase I protection experiments, that purified gamma delta transposase binds at the transposon's inverted repeats (IRs). Immediately adjacent to each transposase binding site (and within gamma delta DNA) we have identified a binding site for an additional protein factor, the Escherichia coli‐encoded integration host factor (IHF). The binding of transposase and IHF to these adjacent sites is mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 28 publications
2
42
0
Order By: Relevance
“…Thus, the timing of transposition of certain elements is at least partially correlated with the cell replication cycle. Other biochemical and genetic studies have identified host factors, such as integration host factor, histone-like nucleoid structuring protein, and Hu, as playing an important-but not essentialrole in transposition of many elements (30,41,51,52,55). Indeed, the observation that these nucleoid-associated proteins can influence both transposition and site-specific recombination reinforces the proposal that these proteins communicate cellular status to the recombination machinery (6,53).…”
mentioning
confidence: 78%
“…Thus, the timing of transposition of certain elements is at least partially correlated with the cell replication cycle. Other biochemical and genetic studies have identified host factors, such as integration host factor, histone-like nucleoid structuring protein, and Hu, as playing an important-but not essentialrole in transposition of many elements (30,41,51,52,55). Indeed, the observation that these nucleoid-associated proteins can influence both transposition and site-specific recombination reinforces the proposal that these proteins communicate cellular status to the recombination machinery (6,53).…”
mentioning
confidence: 78%
“…IHF modulates Tn10 transposition in vivo and in vitro; IHF stimulates Tn10 excision and forces transposon end-target DNA interactions into a constrained pathway that yields only unknotted intratransposon inversion circles (3,54). IHF binds to the ends of ␥␦, a Tn3 family element, cooperatively with transposase and stimulates transpositional immunity of ␥␦ (67,68). Fis is required for various site-specific recombination systems, and HU and IHF act in some of these systems as well (for a review, see reference 12).…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest that IHF can stimulate translation initiation (35) and transcription initiation (6,17,18,24,25,48) and elongation (59). In some of these systems (17,24,57), and in other processes (4,44,47), IHF has been found to alter DNA structure and influence the function of other DNA-binding proteins (25,47,61). Therefore, the negative effect of IHF on ompB transcription may be more complex than a simple model of direct interaction between IHF and RNA polymerase.…”
Section: Methodsmentioning
confidence: 99%